Gene expression in human chondrocytes in late osteoarthritis is changed in both fibrillated and intact cartilage without evidence of generalised chondrocyte hypertrophy. Issue 01 (22nd December 2008) - Brew, C J; Clegg, P D; Boot-Handford, R P; Andrew, J G; Hardingham, T
Abstract : Objectives: To investigate changes in gene expression in fibrillated and intact human osteoarthritis (OA) cartilage for evidence of an altered chondrocyte phenotype and hypertrophy. Methods: Paired osteochondral samples were taken from a high-load site and a low-load site from 25 OA joints and were compared with eight similar paired samples from age-matched controls. Gene expression of key matrix and regulatory genes was analysed by quantitative real-time reverse transcription-polymerase chain reaction on total RNA extracted from the cartilage. Results: There was a major change in chondrocyte gene expression in OA cartilage. SOX9 (38-fold) and aggrecan (4-fold) gene expression were both lower in OA (p<0.001), and collagen I (17-fold) and II (2.5-fold) gene expression were each increased in a subset of OA samples. The major changes in gene expression were similar at the fibrillated high-loaded site and the intact low-loaded site. There was no evidence of a generalised change in OA to proliferative or hypertrophic phenotype as seen in the growth plate, as genes associated with either stage of differentiation were unchanged (PTHrPR), or significantly downregulated (collagen X (14-fold, p<0.002), VEGF (23-fold, p<0.02), BCL-2 (5.6-fold, p<0.001), matrilin-1 (6.5-fold, p<0.001)). In contrast MMP-13 was significantly upregulated in the OA cartilage samples (5.3-fold, p<0.003). Conclusions: The expression of key chondrocyte genes, including aggrecan and SOX9, was decreased in OA cartilage and the changes were similar in both fibrillated high-loaded and intact low-loaded cartilage on the same joint. However, there was no significant upregulation of type X collagen, and other genes associated with chondrocyte further differentiation and hypertrophy.